Solving the South China Sea Crisis: A Recommendation for Indonesia - Kevin Ramadhan Sandy (Andalas Journal of International Studies (AJIS))
The main purpose of this paper is to recommend to Indonesia to maintain its national interest of a unified ASEAN on the South China Sea disputes with four policy recommendations. The failure of the 2012 ASEAN Ministerial Meeting was observed as many analysts as the start of a crack in ASEAN as a regional group. With Cambodia’s acting as China’s proxy in the meeting, ASEAN failed to address the issue and to put it in the Joint Communique, although Vietnam and Philippines have insisted the chair to do so. This event led to the rise of suspicions from ASEAN claimant states towards Cambodia and China’s intention. Furthermore, this becomes a proof that ASEAN could no longer be independent as a regional group as China has increased its economic leverage on Cambodia. At the same time, Philippines and Vietnam have increased their bilateral ties with the United States, hoping to increase their leverage and capability vis-à-vis China. Thus, ASEAN is in an unstable state with high possibility of it to be divided into two blocs with the South China Sea still unresolved. One of Indonesia’s main foreign policy interests is a unified, centralized and independent ASEAN as a regional bloc. President Yudhoyono and Foreign Minister Natalegawa reflected this by underscoring the importance of ASEAN and the need to resolve the dispute as soon as possible before further tension occurred. In this case, Indonesia should try to act as the mediator to solve this issue as a neutral player.